EFEKTIVITAS LUDO WORD GAME (LWG) DALAM MENINGKATKAN PENGUASAAN KOSAKATA BAHASA JEPANG PADA SISWA KELAS XI SMK KANSAI PEKANBARU - Ramadinni, Nurul Hayati; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to determine the effectiveness of Ludo Word Game(LWG) in improving Japanese vocabulary mastery in class XI students of SMK KansaiPekanbaru. Based on the results of the researcher's observations during the Japaneselanguage learning process, it shows that students tend to have poor concentration inlearning, and low vocabulary mastery, which results in low student completion rates.The type of research used in this study is quantitative in the form of True Experimentalwith the research design used is Pretest-Posttest Control Group Design. Data collectionwas carried out by distributing Pre-test Post-test, providing treatment, and conductingdata analysis. The sample in this study amounted to 54 respondents and was determinedbased on the Simple Random Sampling technique. Based on the results of the study, itshows that there is an increase in Japanese vocabulary mastery using Ludo Word Game(LWG) compared to students who were not given treatment with Ludo Word Game. Inaddition, students in the experimental class looked more enthusiastic and active inlearning Japanese. While in the control class that uses conventional learning methods,students looked less enthusiastic during Japanese language learning.Keywords: Effectiveness: Ludo Word Game: Vocabulary Master